Pigmen aktinomiset: potensi dan pemanfaatannya di berbagai bidang - Purwaningtyas, Widya Esti; Sholekha, Siti; Cahlia, Uci (Program Pascasarjana Universitas Papua, 2026)
Synthetic pigments are increasingly scrutinized due to concerns over toxicity, bioaccumulation, and environmental pollution, which has intensified global interest in natural pigments as safer and more environmentally responsible alternatives. Among microbial producers, actinomycetes stand out as a highly promising source because they are capable of synthesizing a wide spectrum of pigments, including melanin, prodigiosin, carotenoids, actinorhodin, and other chromogenic metabolites that function not only as coloring agents but also exhibit valuable biological activities such as antimicrobial, antioxidant, photoprotective, and anticancer effects. These multifunctional properties expand their relevance across numerous fields, including food, cosmetics, textiles, pharmaceuticals, agriculture, and biotechnology. Despite this broad potential, large-scale utilization of actinomycete-derived pigments remains constrained by challenges such as low or inconsistent yields, variability in pigment quality, relatively high production costs, and the need for complex downstream purification. Advances in fermentation optimization, the development of cost-effective substrates, and the application of metabolic and genetic engineering are helping to address these limitations and improve production feasibility. In this context, the present review aims to provide an overview of pigment types produced by actinomycetes, highlight their functional and industrial applications, and discuss the key obstacles and future prospects for their development as competitive natural colorants.